KEUANGAN MIKRO PADA KOPERASI KONSUMEN SYARIAH: MENINGKATKAN EFISIENSI DAN KEBERLANJUTAN DI ERA DIGITALISASI DAN EKONOMI KREATIF - Hani’atul Latifah, Nur; Rahmadanie, Dhea; Sevia Tamara, Alda; Amalia, Varissa; B, Irwan (Ekonomi Syariah STAI Sangatta Kutai Timur, 2025)
Microfinance management in Islamic consumer cooperatives is a field that continues to grow in line with technological innovation and digital economic development. This study uses a qualitative method with a literature-study approach to examine various relevant concepts and theories in Sharia-based microfinance management. The discussion focuses on the concept of technological innovation, small-scale digital financial management, and the influence of the creative economy on the Islamic microfinance model. In addition, the Technology Acceptance Model (TAM) is studied to understand the acceptance of digitalization by cooperatives and Sharia MSMEs. This study shows that integrating Sharia principles such as justice, trust, and benefit with digital innovation and the creative economy can improve the efficiency, transparency, and sustainability of microfinance management. It confirms that developing digital-based microfinance from a Sharia perspective has great potential to strengthen governance, increase inclusivity, and adapt to modern economic dynamics.